Peningkatan Kapasitas Remaja Untuk Mencegah Obesistas Melalui Kampanye Piringku Model T Sman 10 Kota Jambi - Putra, Egy Sunanda; Irfan, Ary (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Obesity is still a nutritional problem in developed and developing countries. Obesity or stomach disease occurs in adolescents aged >15 years. One of the efforts to prevent adolescent obesity is to control body weight through changes in eating patterns by promoting the slogan "fill my plate, model T" as a healthy behavior for adolescents through nutritional education. The aim of the activity is to increase the capacity of teenagers to prevent obesity through the My Plate Model T campaign. Teenagers who took part in this activity had a previous average score of 6.40 to 9.20, eating patterns of 5.60 to 8.45. Service activities increase knowledge and improve diet in preventing central obesity in adolescents.